2017
DOI: 10.3389/fphys.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Role of NADPH Oxidase-4 in Human Endothelial Progenitor Cells

Abstract: Introduction: Endothelial progenitor cells (EPCs) display a unique ability to promote angiogenesis and restore endothelial function in injured blood vessels. NADPH oxidase 4 (NOX4)-derived hydrogen peroxide (H2O2) serves as a signaling molecule and promotes endothelial cell proliferation and migration as well as protecting against cell death. However, the role of NOX4 in EPC function is not completely understood.Methods: EPCs were isolated from human saphenous vein and mammary artery discarded during bypass su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 79 publications
(120 reference statements)
0
15
2
Order By: Relevance
“…The transplantation of integrin β1-overexpressing ECFCs restored the local vascular network by physically engrafting within neovessels and rescued local blood flow [ 230 ]. A recent investigation focused on NADPH oxidase 4 (NOX4) [ 233 ], which is constitutively active and promotes H 2 O 2 production, thereby stimulating ECFC proliferation and migration [ 234 ]. NOX4 overexpression stimulated ECFC migration in vitro, albeit this effect was mediated by enhanced anion superoxide, rather than H 2 O 2 , production.…”
Section: Genetic Manipulation Of Pro-angiogenic Signaling Pathwaysmentioning
confidence: 99%
“…The transplantation of integrin β1-overexpressing ECFCs restored the local vascular network by physically engrafting within neovessels and rescued local blood flow [ 230 ]. A recent investigation focused on NADPH oxidase 4 (NOX4) [ 233 ], which is constitutively active and promotes H 2 O 2 production, thereby stimulating ECFC proliferation and migration [ 234 ]. NOX4 overexpression stimulated ECFC migration in vitro, albeit this effect was mediated by enhanced anion superoxide, rather than H 2 O 2 , production.…”
Section: Genetic Manipulation Of Pro-angiogenic Signaling Pathwaysmentioning
confidence: 99%
“…Although we have demonstrated that effects of NADPH oxidase activation in neuronal death after hypoglycemia [ 26 ], traumatic brain injury [ 22 ], and epilepsy [ 21 ], the efficacy of inhibition of NADPH oxidase activation by apocynin treatment in seizure-induced neurogenesis has not been demonstrated. We hypothesized that, if ROS are constantly produced after a seizure, the rate of newly proliferated neuronal survival is reduced as a function of the ROS production [ 29 , 30 , 31 ]. In the present study, we found that the survival rate and neurogenesis of hippocampal cells after seizure induction was increased via inhibition of NADPH oxidase.…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation of integrin β1-overexpressing ECFCs restored the local vascular network by physically engrafting within neovessels and rescued local blood flow [252]. A recent investigation focused on NADPH oxidase 4 (NOX4) [255], which is constitutively active and promotes H2O2 production, thereby stimulating ECFC proliferation and migration [256]. NOX4 overexpression stimulated ECFC migration in vitro, albeit this effect was mediated by enhanced anion superoxide, rather than H2O2, production.…”
Section: Genetic Manipulation Of Pro-angiogenic Signalling Pathways Imentioning
confidence: 99%